PEMANFAATAN BUAH SUKUN (Artocarpus Altilis) DENGAN PENAMBAHAN SUSU ULTRA HIGH TEMPERATURE (UHT) DALAM PEMBUATAN YOGHURT SABAGAI RANCANGAN MODUL PEMBELAJARAN BIOLOGI DI SMA - Satifa, Nabela Ida Coriza; Mahadi, Imam; Sayuti, Irda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted in May and June 2016. The study was carried out by two stages. Phase I of making yoghurt breadfruit (Artocarpus altilis) with the method used in this study is the experimental method. Making yogurt breadfruit (Artocarpus altilis) begins with the stage of pasteurization, refrigeration, innokulasi and incubation. The parameters in this study include lactic acid levels, pH and protein content. UHT milk 20ml Extra showed significant gains against the yoghurt breadfruit (Artocarpus altilis) with a mean of 0.96% lactic acid levels, pH 3.8 and the protein content of 6.36%. Phase II is the stage of designing the module by analyzing the curriculum in 2013, KD and Syllabus. The analysis showed that KD potential in the design of conventional modules on biotechnology in the field of food was KD 3:10.Key Words: Lactic acid bacteria, UHT milk, breadfruit, Modules